SISTEM PENDUKUNG KEPUTUSAN MENENTUKAN PENERIMA BEASISWA MENGGUNAKAN METODE COMPARATIVE PERFORMANCE INDEKS PADA SMK AL-HIKMAH - Amalia Adilah Putri; Kiki Kusumawati (FAKULTAS TEKNIK, 2021)
Scholarships annually awarded to students who Excel. In determining the recipients of the scholarship, the homeroom teacher should collect data on student achievers that get ranked top three in each class to get the big three in every department. The methods that will be used to determine the scholarship recipient using the method of Comparative Performance Index (CPI). This method is able to transform different scales so that retrieved the value of alternatives which will help in the decision making. The results of the calculation of the decision support system using the method of Comparative Performance Index (CPI) is based on the value of alternative and ranking for ease in determining who is the grantee